Structural Insights into the PorK and PorN Components of the Porphyromonas gingivalis Type IX Secretion System. - Dhana G Gorasia; Paul D Veith; Eric G Hanssen; Michelle D Glew; Keiko Sato; Hideharu Yukitake; Koji Nakayama; Eric C Reynolds (PLoS Pathogens)
The type IX secretion system (T9SS) has been recently discovered and is specific to Bacteroidetes species. Porphyromonas gingivalis, a keystone pathogen for periodontitis, utilizes the T9SS to transport many proteins including the gingipain virulence factors across the outer membrane and attach them to the cell surface via a sortase-like mechanism. At least 11 proteins have been identified as components of the T9SS including PorK, PorL, PorM, PorN and PorP, however the precise roles of most of these proteins have not been elucidated and the structural organization of these components is unknown. In this study, we purified PorK and PorN complexes from P. gingivalis and using electron microscopy we have shown that PorN and the PorK lipoprotein interact to form a 50 nm diameter ring-shaped structure containing approximately 32-36 subunits of each protein. The formation of these rings was dependent on both PorK and PorN, but was independent of PorL, PorM and PorP. PorL and PorM were found to form a separate stable complex. PorK and PorN were protected from proteinase K cleavage when present in undisrupted cells, but were rapidly degraded when the cells were lysed, which together with bioinformatic analyses suggests that these proteins are exposed in the periplasm and anchored to the outer membrane via the PorK lipid. Chemical cross-linking and mass spectrometry analyses confirmed the interaction between PorK and PorN and further revealed that they interact with the PG0189 outer membrane protein. Furthermore, we established that PorN was required for the stable expression of PorK, PorL and PorM. Collectively, these results suggest that the ring-shaped PorK/N complex may form part of the secretion channel of the T9SS. This is the first report showing the structural organization of any T9SS component.